Underground: marginalidade e contracultura em A fúria do corpo, de João Gilberto Noll - Thales Saymon Mendes Cunha (2014)
This study is based in the opposite relations between authoritarianism and resistance in the romance A fúria do corpo by João Gilberto Noll. The porto-alegrense author is one of the contemporary Brazilian literature authors that have renounced the traditional representation ways adopting alternative procedures of literary production. The romance addresses a peripheral world bared of a national idealism, conservative and totalitarian. This thesis peers in this way the relationship between this romance and a political and cultural movement that had its beginning in the 60s, the one well known as counterculture. We have explored the subversive components present in the mentioned narrative observing the resistance position that it assumes in the presence of violence and authoritarianism found, above all, in the military dictatorship period in Brazil. We have also discussed the marginality representation, especially from the characters, besides reflecting about the wandering principle and about the permanent traffic of characters in the romance, relating to the North-American movement beat.